A molecular investigation of β-thalassemia in the Aegean and Mediterranean coasts of Turkey :|is there a region-dependent specificity? - Senga, Edward Bisweck. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1994., 1994)
As in many other Mediterranean countries, β-Thalassemia is also a major public health concern in Turkey. The average gene frequency.is estimated to be two per cent, and regions with higher figures are known to exist. Country scale frequencies of β-thalassemia mutations have been established in Turkey by several investigators in the past, but mutational data maps at regional scale are not available yet. The present study was designed to investigate the presence of a possible locus-specific heterogeneity of β-thalassemia mutations at the Aegean and the Mediterranean coasts of Turkey. Blood samples of patients sent to our laboratory from the Medical Schools in Izrnir, Antalya and Adana were chosen as being representative for the Western and Southern parts of the country. The method of choice for screening a large number of chromosomes for point mutations, involves the PCR amplification of the gene under investigation, followed by hybridization of the amplified DNA to Allele Specific Oligonucleotide (ASO) probes. A total of 191 chromosomes were analyzed in the framework of this thesis using 19 oligonucleotide probes specific for the Mediterranean countries. The results obtained do confirm the remarkable molecular heterogeneity of β-thalassemia in all three districts investigated. Although a marked locus-specific heterogeneity of mutations was not observed, different patterns of mutational distribution were obvious, which may help in the elucidation of the molecular heterogeneity of Turkey in certain cases.
Keywords: Thalassemia -- Turkey.; Hemoglobinopathy.